THE EFFECT OF PANHISTERECTOMIZED AND HIGH PHOSPHORUS INTAKES ON CALCIUM AND PHOSPHATE ANORGANIC CONCENTRATION IN THE BLOOD, AND THE BONE CHANGES IN RATS - Hartiningsih Hartiningsih (Jurnal Sain Veteriner, 1999)
Estrogen is an inhibitor of bone resorption. Although there is some disagreement, most studies indicated that bone loss is accelarated at the time of menopause wether it is induced surgically or naturally. When the condition mentioned above is supported by imbalance diet, especially calcium to phosphor ratio, the bone loss will be accelarated. The obyectlves of the research were to study the effect of panhisterectomized and high phosphorous intake on calcium and phosphate anorganic concentration in the blood, and bone changes in rats.Sixteen female of rats ± 30 days of age were randomly divided into four groups (A, B. C, and DJ of four each. The group A and C were unpanhisterectomized. Whereas the group B and D were panhisterectomized. The group A and B were fed diet contain Ca:P ratio = 1.5:1, whereas the ratio of calcium and phosphorus 1.5:6 was given to group C and D. At the end of the experiment, the blood samples were taken directly from eye (plexus retroorbitalis) for calcium and phosphate analysis. The left femur were taken for histopathological analysis.From the results can be concluded that the diet containing the Ca:P in variation ratio, panhistcrectomized. and interaction between two of them had significant effect on the blood inorganic phosphate (P < 0,01). The diet containing CaiP = 1.5:6 for unpahisterectomized caused earliest lesion of osteodistrphia fibrosa, whereas for panhisterec-tomized caused mild osteodistrophia fibrosa.